Summary of updates to the 2021 European Society of Cardiology Guidelines for the diagnosis and treatment of acute and chronic heart failure - V. N. Larina; I. K. Skiba; A. S. Skiba (Российский кардиологический журнал, 2022)
The article provides a summary of the 2021 European Society of Cardiology (ESC) Guidelines for the diagnosis and treatment of acute and chronic heart failure (CHF). The most significant changes for general practitioners, internists and primary care cardiologists, from our point of view, regards etiology, terminology, as well as algorithms for diagnosing and treating CHF in accordance with phenotypes, new indications to a number of drugs, in particular sodium-glucose cotransporter type 2 inhibitors (dapagliflozin and empagliflozin) with assignment of class I recommended therapy and vericiguat. The article discusses the diagnostic criteria for different heart failure phenotypes, the potential of treating patients with heart failure mildly reduced and preserved ejection fraction.